Analisi Instrumen Penilaian Diri Pada Mata Pelajaran Al-Qur'an Hadits di Kelas VII Madrasah Tsanawiyah Raudhatul Iman - Hasanah, Uswatun; Remiswal; Khadijah (PAI RAFAH, 2025)
Based on the phenomenon of the behavior of students in the era of information globalization and various teacher constraints in character assessment, it is very important to conduct self-assessment of students in the era of globalization, especially in the subject of Al-Qur'an Hadith. This Self-Assessment Instrument aims to provide a clear picture of the importance of conducting self-assessment in Al-Qur'an Hadith subjects for students in learning related to the Qur'an, as initial information for teachers, educational institutions, and the government in the context of educational development, as well as a reference for anyone who will conduct further student self-assessment research. The method in this study uses a qualitative method with a phenomenon approach. The result obtained is that the self-assessment instrument in the Qur'an Hadith subject becomes very important to be carried out. The self-assessment instrument on students periodically and effectively.